SYSTEMATIC LITERATURE REVIEW: THE ROLE OF DIGITAL INFLUENCERS IN DIGITAL MARKETING - Krisnawati, Vivi; Pebrianggara, Alshaf; Andry Rachmadany; Prasojo , Bayu Hari (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study is to determine and examine how digital influencers fit into digital marketing plans. Because of their extensive audience influence, digital influencers are now essential components of contemporary marketing. Methods: This study takes a descriptive qualitative approach and employs a systematic literature review strategy. Results: The study concluded that influencers are crucial in raising brand recognition, establishing reputation, and influencing customer purchase decisions based on the body of available literature. Influencers can establish a more intimate connection between brands and customers by producing genuine content that resonates with their audience. However, choosing the correct influencers and matching their values with the company being pushed are crucial to the success of influencer-based marketing initiatives. Novelty: According to the study's findings, influencer marketing has a lot of potential for digital marketing, but in order to be as successful as possible, rigorous planning and control are needed.